Paleogeographic and litho-facies formation conditions of MidUpper Jurassic sediments in S-E Western Siberia (Tomsk Oblast) - Shaminova, Marina Ivanovna; Rychkova, Irina Vladimirovna; Sterzhanova, Ju. (IOP Publishing, 2016)
This paper describes the criteria to identify Tumen (lower Bathonian) and Naunak (upper Bathonian-Callovian- Oxfordian) suites within S-E Western Siberia (Tomsk Oblast). The specific paleogeographic and litho-facies formation conditions of sediments and numerous vegetable remains and ichnofossils indicated the fact that this territory was the location of sedimentogenesis transition during Tumen and Naunak suite formation. Based on integrated survey oil-gas potential litho-facies groups were defined in Mid-Upper Jurassic sediments within S-E Western Siberia.
Keywords: литофации; верхнеюрские отложения; Западная Сибирь; Томская область; седиментогенез; месторождения; нефти; газы